KAJIAN BUNGA MAWAR SEBAGAI SIMBOL BUDAYA LOKAL DAN AGAMA MELALUI PANDANGAN SEMIOTIKA ROLAND BARTHES - Aziz Al Bilad (Fakultas Ilmu Budaya, Universitas Brawijaya, 2021)
Until now, the rose has various meanings, namely as a symbol of love, beauty, respect, and joy and sorrow. There are lots of red roses that are very popular with many people. Like the flame on a red rose which is used as a symbol of affection. But apart from being a rose that has been applied above, flowers are also widely used for cultural and religious purposes. For example in culture, namely the Javanese custom which uses roses as a wedding ceremony, and roses as a death ceremony. In the formulation of the research problem, what is the meaning of denotation, connotation, and myth in roses as symbols of local culture and religion through Roland Barthes' semiotic method. The purpose of this research is to describe and examine the meaning of the rose symbol through denotation, connotation, and myth. From the research results, it can be seen that the denotation of roses or rose petals and the connotation of red roses is a symbol of affection.